(untitled) (Jurnal Penelitian Kehutanan Wallacea, 2012)
Fermentation is a natural process that happen in fresh-sweet sap of aren trees (Arenga pinnata Merr.), because many kinds of microorganism stay and life in this substance e.g. bakteria (Acetobacter acetic) and yeast (Saccharomyces tuac). Species of yeast from genus of Saccharomyses, e.g. Saccharomyses serivisae is wellknown as microorganism that can ferment sugar (glucose) into alchohol and CO2. This natural process as well happen in aren sap, so that this substance potencially using as a swollen agent of bread or cake dough. This research objective is to recognize the effectiveness of aren sap as a swollen agent of bread dough. Fermentation duration of bread dough was one hour by using swollen agent of fresh, 10 hours old and 20 hours old of aren sap. Daily yield of sap tapped from aren trees in Maros district, South Sulawesi province was 7 litre (4-5 litre collected in the morning and 2-3 litre colected in the afternoon). Aren sap containt some of nutritions e.g. carbohydrate, protein, fat, vitamin C and mineral. Sweet taste of aren sap caused by it’s charbohydrate content of 11.18%. The effectiveness of aren sap as a swollen agent of bread dough is lower than instant (commercial) yeast. The older of aren sap the lower of it’s effectiveness as a swollen agent of dough and kuality of bread yield.